Elements of a financial projection included in rural areas entrepreneurship development funds acquisition applications as exemplified by the RADP and ROP OV - Pieczonka, Jacek (Wybrane aspekty projekcji finansowej zawartej w wnioskach o pozyskanie środków na rozwój przedsiębiorczości na przykładach EFRROW i RPO WO, 2011)
A business plan as an expression of a financial projection is an element supporting an entrepreneur in the decision-making process concerning business development. The preparation of a business plan is a supporting element in the management process; and thus also a supporting element in entrepreneurship. It is important for the structure, scope of details and difficulty of a business plan (including also an Economic Operational Plan) to be adjusted to the organizational possibilities of the entrepreneur and the amount of subsidies applied for
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 33-43
Keywords: business plan; economic operational plan; financial projection; entrepreneurship; RADP; ROP OV